Microwave hydrothermal synthesis and upconversion properties of BiVO4 nanoparticles - Kshetri, Yuwaraj K; Regmi, Chhabilal; Dhakal, Dhani Ram; Kim, Tae-Ho; Kim, Seung Ho; Kim, Hak-Soo; Lee, Soo Wohn (Nanotechnology, 2020)
Nanomaterials are the subject of extensive investigations due to their applications in medicine, multimodal imaging, volumetric displays, and photonics. Here, lanthanide-doped bismuth vanadate (BiVO4) upconverting nanoparticles (UCNPs) have been reported. The nanoparticles have been synthesized by a microwave hydrothermal method. As-synthesized nanoparticles are highly crystalline in the tetragonal zircon phase with particles about 200 nm in size. Under 980 nm excitation, intense multicolor visible and near-infrared upconversion emissions are observed. Moreover, broadband infrared downshifting emissions are also observed. Time-resolved emission measurements have been carried out to investigate the involved upconversion and energy transfer mechanism. The BiVO4-based UCNPs may provide a new class of nanomaterials for multifunctional applications.